THE THEOLOGICAL PERSPECTIVES TOWARD COVID-19: A PRELIMINARY STUDY OF TABLIGH JEMAAH IN MAKASSAR, INDONESIA - Muhaemin Latif; Hamdan Juhannis (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
The study discusses the theological perspectives of Jemaah Tabligh (hereafter: JT) in Makassar in contending COVID 19. It employs qualitative research methodology through conducting observation, focusing on group discussion, and document collection. Two different groups of JT become the object of interview, JT Seluruh Alam and JT Maulana Saad (MS). The researchers picked up some crucial figures from JT members. The research found that the theological perspectives of JT regarding COVID 19 from two different schools of theology, Jabariah (fatalism) and Asy’ariyah. The researcher concluded that Jabariah influenced the attitudes of JT Maulana Saad, and Asy’ariyah affected the way of thinking of JT seluruh alam. Both different schools of theology existed in the life of JT, not only in the context of COVID 19 but also in public life. Besides, the internal dispute of JT in India influenced the thinking among JT adherents in Makassar.